A practical guide to workload management and injury prevention in college and high school sports - Gazzano, F.; Gabbett, T. (NSCA Coach, 2016)
Sports injuries are a widespread problem at college and high school. In the United States alone, 1.5 million high school and college athletes are injured every year (12,18). The cause of injuries is often multifactorial; however, recent research has identified that poor workload management may be a major contributor to injuries and illnesses in sport (5,7,20,25). This article will present evidence-based workload management recommendations to reduce the risk of illness and injury in athletes, while also optimizing performance.